Weight Watchers rebrands to WW - Osland, Asbjørn; Clinch, Nanette (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Weight Watchers has rebranded itself to WW, where the emphasis is wellness, with Oprah Winfrey as a shareholder and spokesperson. Critics see the WW rebranding as superficial, with a continued focus on weight loss, and believe people should feel comfortable at their current weight. Initially, the shift to wellness with Winfrey's investment and support brought about membership growth and increases in revenues and share price in 2017. However, WW shares have declined due to a fall in subscriptions in early 2019; a decline so great that law firms were suing WW's management for violation of U.S. Securities and Exchange Commission (SEC) rules. The rebranding was not enough to put WW on a trajectory of increasing profits. WW's promotion of their Freestyle program, an approach to weight loss and maintenance in the wellness context, espoused by Oprah Winfrey, has not led to sustained earnings growth.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; WW International -- Marketing -- Case studies; Branding (Marketing) -- Case studies